The future of standardized sustainability reporting - Tia Rebecca Driver; Amr El Alfy; Olaf Weber (Centre for International Governance Innovation (CIGI), 2023)
Regulators and stakeholders demand reliable, valid and comparable information about a company's operations - and increasingly, not only its financial performance, but its non-financial impacts on society and the natural environment. Accordingly, regulators and reporting entities have developed sustainability reporting standards, but these are grounded in different reporting goals and sometimes in conflict. In this paper, Tia Rebecca Driver, Amr ElAlfy and Olaf Weber contribute to the current discussion of standardized sustainability reporting by analyzing the landscape of reporting frameworks and their governance bodies, which oversee and work on the standardization of sustainability reporting. They provide contextual background on the governance of sustainability reporting by comparing the prominent reporting frameworks to understand how they complement or conflict with one another. They then investigate the impact of mandatory reporting and materiality to understand how these concepts could influence the application and extensiveness of a composite reporting standard. Finally, the authors provide policy makers with recommendations that facilitate a standardized reporting approach that centres on sustainable development.
Keywords: 330